Public Knowledge About The Importance Of Death Certificates - Tutik Purwanti (Universitas Muhammadiyah Malang, 2025)
Background: A death certificate is an important legal document, yet it is not well-managed and its recording is still low. In addition to determining the cause of death and completing various administrative processes, this document is also used for managing national population data and determining health policies. This problem arises primarily due to a lack of awareness about the importance of death registration. Purpose: To Increase knowledge about the importance of death certificate. Methods: Provide counseling, discussion, and practice in writing death certificate for community health center employees, assess pre-post knowledge through questionnaires. Results: The counseling activity was conducted on Saturday, June 24, 2023, at the Bendo Community Health Center Auditorium, located at Jl. Soekarno Hatta No.27, Bendo Kidul, Bendo, Pare District, Kediri Regency, East Java 64225, from 11:30 AM until finished WIB with total 24 participants. Conclusion: Pre-post test result indicate that participants have gained a better understanding and awareness of the importance of death certificates.